The distribution of serotonergic nerve on the hippocampus of the fruit bats (Rousettus amplexicaudatus) - Vivin Wirawati; Nourrisma D. A. Widiati; Geraldus Gunawan; Golda R. Saragih; Puspa Hening; Hevi Wihadmadyatami (Veterinary World, 2019)
Background: Rousettus amplexicaudatus is one of the old world fruit bats, commonly known in Javanese word as codot belongs to Order Chiroptera and suborder Megachiroptera. R. amplexicaudatus possessed an outstanding visual ability, which helps in the process of searching for food. Those activities process and save within the brain involving the learning and memory activities. Learning and memory activities are centered around the hippocampus with the help of serotonergic nerve.